The effectiveness of guidance group services using the semantic precision technique to improve self-confidence in junior high school students - Rakipah; Nasution, Fauziah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Low self-confidence is a common issue among junior high school students, especially during adolescence, which is a period of identity searching. This study aims to improve the self-confidence of students at junior high school IT Al Hijrah by using group counseling services with the Semantic Precision technique. The study employed a pre-experimental design with a single group and involved 21 students as samples. Data were collected through observations, interviews, instruments, and documentation. The results showed a significant increase in students’ self-confidence, with an average pre-test score of 73.10 and a post-test score of 89.29, indicating an improvement of 16.19 points.